Farmer’s knowledge and willingness to apply sustainable agricultural intensification options in arid and semi-arid areas in Benin - SEGNON, ALCADE C.; Achigan-Dako, Enoch Gbenato; Orou, Gaoue; VODOUHE, RAYMOND; N'Danikou, Sognigbé; AHANCHEDE, ADAM (My University, 2015)
Building on farmer’s agroecological knowledge to design environmental-friendly agricultural systems is crucial given the environmental impact of industrial agriculture. We investigated the drivers of farmers’ knowledge of agrobiodiversity management and analyzed how farmers’ knowledge and their current farming contexts may guide future farming systems in sub-humid (Bassila) and semi-arid (Boukoumbé) areas of Benin. We conducted structured interviews with 180 farmers and used generalized linear models and correlation analyses to understand the spatio-temporal dynamics of farmers’ knowledge and perception. Land tenure, ecological conditions and sociolinguistic membership were the main drivers of farmers’ knowledge of agroforestry systems, practices, species diversity and current farming systems. Sociolinguistic membership also significantly predicted farmers’ knowledge of livestock management. Farmers in the semi-arid area were more involved in integrated crop-tree-livestock systems than those in the sub-humid area. However, all farmers indicated a willingness to adopt this integrated farming system regardless of socioeconomic and ecological factors. Farmer’s knowledge of agrobiodiversity (crops, agroforestry species and livestock diversity) management was correlated with the involvement in integrated crop-livestock-tree and agroforestry systems. These findings provide insights into how farmers’ knowledge can serve as basis in optimizing agricultural and livelihoods systems. Investigating the ecological, economic and social performance of the most desired integration/diversification options using a system approach involving a co-innovation process can further our mechanistic understanding of farmers decision making process.
Keywords: local ecological knowledge; crop-tree-livestock systems; agroforestry systems; agrobiodiversity; integrated agro-ecosystem approach; Benin